Ответы и объяснения

2014-03-04T17:51:14+04:00
Решение: 
2х-5,5=3(2х-1,5) 
3(2х-1,5)=2х-5,5 
6х-4,5=2х-5,5 
6х-2х=4,5-5,5 
2х=-1 
х=-1/2=-0,5 
Ответ: х=-0,5
я думаю так
Комментарий удален
а) 2х +3

_____ - 8 =0

5

б) 4х - 3 2х +1

____ = ______

5 2

в) х + 2 4х - 3 5 - х

-------- + ---------- - ------- = 1

3 2 6

г) х + 1 х - 4 2х - 1

3 - --------- - --------- + --------- = 0

5 2 10

а)(2х+3)\5-8=0

(2х+3)\5=8

2х+3=8*5

2х+3=40

2х=40-3
3-2x-1=5
(х2-1)/3=(2х-1)/5 +2

Общий знаменатель 15.

5(х2-1)/15 = 3(2х-1)/15 +2*15/15

5(х2-1) = 3(2х-1) +2*15

5х2 -5 = 6х -3 + 30

5х2 - 6х -32 = 0

х=-2 х= 16/5
2014-03-04T17:51:56+04:00
-6x-3=5
-6x=5-3
-6x=2
x= -3

ВОТ!!!! 3-(2х+1)=5
3-2x-1=5
-2x-1=5-3
-2x-1=2
-2x=2+1
-2x=3
2x=-3
x=-3/2
x=-1.5
дошло...
неужели это так сложно
вот вот. Это моя сестренка с 4ого класса решила))
ппц